Carbon emissions of china's industrial sectors based on input–output analysis. Issue 2 (3rd April 2017) - Yu, Xiaohong; Xu, Miao; Ding, Yumeng
ABSTRACT: This study uses an input–output model presenting the embodied carbon emission in the import–export procedure, as well as the responsibility allocation between China's 35 sectors and 7 main trade partners from 1995 to 2011. Results indicate that the amount of carbon emissions in China's industrial sectors is immense and that the industrial sectors are in serious imbalance. Such imbalance exists mainly in textiles, basic and fabricated metal, electrical and optical equipment, and machinery, among others. Based on the consumer-responsibility principle, the responsibility of 29 departments is reduced. Correspondingly, foreign sectors become more responsible. America, as China's largest trading partner, should account for most of the total responsibility, followed by developed countries such as Japan, South Korea, and Germany.